Multi-Task Learning Based on Stochastic Configuration Networks - Dong, Xue-Mei; Kong, Xudong; Zhang, Xiaoping (Frontiers in Bioengineering and Biotechnology, 2022)
When the human brain learns multiple related or continuous tasks, it will produce knowledge sharing and transfer. Thus, fast and effective task learning can be realized. This idea leads to 5 multi-task learning. The key of multi-task learning is to find the correlation between tasks and establish a fast and effective model based on these relationship information. This paper proposes a multi-task learning framework based on stochastic configuration neural networks. It organically combines the idea of the classical parameter sharing multi-task learning with that of constraint sharing configuration in stochastic configuration neural networks. Moreover, it provides an efficient 10 multi-kernel function selection mechanism. The convergence of the proposed algorithm is proved theoretically. The experiment results on one simulation data set and four real life data sets verify the effectiveness of the proposed algorithm.